Teaching Curriculum Using the Effect Competitive Learning Style According To the Training Network Exercises Learn Some Offensive Skills of Basketball - Emad Toma Radi (Journal of Global Pharma Technology, 2019)
Research objectives of preparing an educational platform for educational units using the teaching and learning style of individual and collective competition according to exercises training network to learn some offensive skills of basketball.The researcher pilot curriculum sample that consisted of the first grade students of faculty of Physical Education in the  Mustansiriyah  University, whose number reaches 57 students divided into three experimental groups used tools and means of information collection and tests the skill and experience of the scientific Choose foundations of exploratory pretest curriculum dimensional tests and statistical means. And then present, analyze and discuss the results of the three aggregates, and then the researcher arrived to conclusions as follow:That the teaching curriculum using competitive learning network, according to the training exercises had a positive impact on learning performance level skilled in the handling of the Invite long over your shoulder shots jumping among students in the sample.Keywords: Teaching curriculum, Competitive learning, Training network exercises and offensive skills.